Nilai Simbolik Rumah Panyai Suku Dayak Mualang Sebagai Etika Hidup Bersama - Valentino, Beno (Balale' : Jurnal Antropologi, 2023)
The Panyai house in the Mualang Dayak tribe is a traditional house of the Dayak tribe in Kalimantan, especially in West Kalimantan. The Panyai House is not only a physical building where the Mualang Dayak people live but is also the building at the heart of the social structure of life. The methodology used in this study is a comparative study and is supported by a literature method in the form of literature that focuses on the theme of this research. In this study, it was found that in the Rumah Panyai tradition of the Dayak Mualang tribe, the ethical values of living together are a strong foundation for establishing harmony and community sustainability. There are several noble values contained in it, namely the values of cooperation, togetherness, respect, and solidarity which are an inseparable part of life in the panyai house. The local wisdom values in the panyai house tradition can guide the development of a more sustainable and responsible life towards nature.